Peran UMKM Jasa dalam Mendorong Pertumbuhan Ekonomi Lokal - Meilani, Ayla Nisha; Nugraha, Hasybi Abdillah; Nuraini Pane, Siti; Maulidia, Indah; Khairani Tambunan, Adila (Teewan Journal Solutions, 2025)
Service MSMEs are no longer just complementary, but have become key actors in the local economic ecosystem. They are able to adapt quickly to market changes, develop innovative services, and make significant contributions to regional economic growth. However, behind this great potential, service MSMEs still face a number of complex structural challenges. This research aims to comprehensively explore the strategic role of service MSMEs in driving local economic growth. Through in-depth analysis that combines qualitative and quantitative approaches, this study seeks to map contributions, identify success factors, and formulate practical recommendations for the development of service MSMEs. The method that will be used in this research is a qualitative approach. The qualitative approach method is one way to collect and analyze data that focuses on a deep understanding of social phenomena or human behavior. With the right support, service MSMEs can become the main foundation for a more inclusive, resilient and sustainable local economy.